Specificity of Subtilin-Mediated Activation of Histidine Kinase SpaK - Geiger, Christoph (Appl Environ Microbiol, 2017)
Autoinduction via two-component systems is a widespread regulatory mechanism that senses environmental and metabolic changes. Although the lantibiotics nisin and subtilin are closely related and share the same lanthionine ring structure, they autoinduce their biosynthesis in a highly specific manner. Subtilin activates only the two-component system SpaRK of Bacillus subtilis, whereas nisin activates solely the two-component system NisRK of Lactococcus lactis. To identify components that determine the specificity of subtilin autoinduction, several variants of the respective lantibiotics were analyzed for their autoinductive capacities. Here, we show that amino acid position 20 is crucial for SpaK activation, as an engineered nisin molecule with phenylalanine at position 20 (nisin N20F) was able to activate SpaK in a specific manner. In combination with the N-terminal tryptophan of subtilin (nisin I1W/N20F), SpaK autoinduction reached almost the level of subtilin-mediated autoinduction. Furthermore, the overall structure of subtilin is also important for its association with the histidine kinase. The destruction of the second lanthionine ring (subtilin C11A, ring B), as well as mutations that interfere with the flexibility of the hinge region located between lanthionine rings C and D (subtilin L21P/Q22P), abolished SpaK autoinduction. Although the C-terminal part of subtilin is needed for efficient SpaK autoinduction, the destruction of lanthionine rings D and E had no measurable impact. Based on these findings, a model for the interaction of subtilin with histidine kinase SpaK was established. IMPORTANCE Although two-component systems are important regulatory systems that sense environmental changes, very little information on the molecular mechanism of sensing or the interaction of the sensor with its respective kinase is available. The strong specificity of linear lantibiotics such as subtilin and nisin for their respective kinases provides an excellent model system to unravel the structural needs of these lantibiotics for activating histidine kinases in a specific manner. More than that, the biosyntheses of lantibiotics are autoinduced via two-component systems. Therefore, an understanding of their interactions with histidine kinases is needed for the biosynthesis of newly engineered peptide antibiotics. Using a Bacillus subtilis-based reporter system, we were able to identify the molecular constraints that are necessary for specific SpaK activation and to provide SpaK specificity to nisin with just two point mutations.